Mesenchymal stem cells reverse thymus aging by reprogramming the DNA methylation of thymic epithelial cells - Zailing Yang; Chuan Tian; Zhixu He; Xiangqing Zhu; Jie He; Hang Pan; Ye Li; Guangping Ruan; XiJun Wu; Xinghua Pan (Regenerative Therapy, 2024)
Background: A decrease in the number and activity of thymic epithelial cells (TECs) is an important factor in thymic degeneration. Mesenchymal stem cells (MSCs) treating thymic ageing is a promising strategy, but the DNA methylation modification mechanism in TECs remains unclear. Methods: Aged rhesus monkeys were treated with MSCs to establish a thymic senescence model, and hematoxylin-eosin (HE) staining, immunofluorescence staining, and ELISA were performed to observe the structure and function of the thymus. TEC aging model and MSCs co-culture system were established to detect DNA methylation modification and transcriptomic changes, correlation analysis between transcription factor methylation and mRNA expression, and q-PCR, immunofluorescence staining, and Western blot were used to identified key genes. Results: MSCs improved the structure and function of thymus in elderly macaque monkeys; reduced the expression levels of β-Gal, P16, and P21; and increased the activity of aging TECs. There were 501 genes with increased methylation in the promoter region in the treated group compared with the untreated group, among which 23 genes were involved in the negative regulation of cell growth, proliferation and apoptosis, while 591 genes had decreased methylation, among which 37 genes were associated with promoting cell growth and proliferation and inhibiting apoptosis. Furthermore, 66 genes showed a negative correlation between promoter methylation levels and gene transcription; specifically, PDE5A, DUOX2, LAMP1 and SVIL were downregulated with increased methylation, inhibiting growth and development, while POLR3G, PGF, CHTF18, KRT17, FOXJ1, NGF, DYRK3, LRP8, CDT1, PRELID1, F2R, KNTC1 and TRIM3 were upregulated with decreased methylation, promoting cell growth. Conclusion: MSCs improve the structure and function of aged thymus, which involves the regulation of DNA methylation profiles and a decrease in the methylation level of the transcription factor NGF to specifically upregulate KRT17 and FOXJ1 to promote the proliferation of TECs.